The Quest For Peace and Justice: Examining the Nexus between Peace Education and Adult Education - Hleziphi Naomie Nyanungo (Adult Education Research Conference, 2009)
The author critically analyzes assumptions embedded in the two fields of practice: peace education and adult education for social change and social action. Preliminary findings from a review of literature from the two fields of practice are presented.